Sustainability of the Legal Profession Amid the Covid-19 Pandemic Situation - Saputro, Damar Sinatria (Faculty of Law Universitas Negeri Semarang, 2020)
The rapid spread of the corona virus certainly affects the disruption of the daily activities of the community both in the area that has been turned into a red zone or even not yet. The provisions for determining national disasters have been stipulated in Law No. 24 of 2007 concerning Disaster Management. In fact, the determination of the status and level of disasters has also been regulated by Presidential Regulation No. 17 of 2018 concerning the Implementation of Disaster Management in Certain Conditions. The virus that sufferers experience symptoms such as fever, dry cough, and difficulty breathing is of course disrupting many sectors, the legal sector certainly is not spared and of course experienced interference. Activities in the field of law are one of the areas that rely heavily on human relations in close proximity. Almost all activities in the field of law require us to be close to other humans. With the corona virus that requires us to keep our distance with others, of course this is very difficult if we want to carry out activities in the field of law that is usually done. Not to mention the fact that the government encourages us to stay at home, then also the closure of various roads that make our Movement very limited.